KERAGAMAN FENOTIPE DAN KEMIRIPAN MORFOLOGIS HANJELI (Coix lacryma-jobi L.) DI KABUPATEN LIMA PULUH KOTA - Ayu Kurnia Illahi (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2020)
[PHENOTYPIC VARIABILITY AND MORPHOLOGICAL SIMILARITY OF JOB’S TEARS (Coix lacryma-jobi L.) IN LIMA PULUH KOTA REGENCY]. Job’s tears (Coix lacryma-jobi L) Has been long known as alternatif food crop and spread over the  West Sumatera Province. This study aims to determine the similarity of job’s tears based on morphological characters. This research was conducted in eight sub districts in Lima Puluh Kota regency. The accessions were observed on  the basis of  purposive sampling method. Data were collected for  29 morphological characteristics  and subjected to the similarity analysis  and cluster analysis using NtSys Ver 2.02i. From the analysis of similarity, job’s tears has a similarity coefficient ranging from 0.07 to 0.63 and shows a distant level of similarity to job’s tears even though they are located close to each other, so that the level of similarity of 74 accessions varies and spreads irregularly.